Quality-of-life analysis of the MITO-8, MaNGO, BGOG-Ov1, AGO-Ovar2.16, ENGOT-Ov1, GCIG study comparing platinum-based versus non-platinum-based chemotherapy in patients with partially platinum-sensitive recurrent ovarian cancer. (16th February 2018) - Piccirillo, M C; Scambia, G; Bologna, A; Signoriello, S; Vergote, I; Baumann, K; Lorusso, D; Murgia, V; Sorio, R; Ferrandina, G; Sacco, C; Cormio, G; et al.
Abstract: Background: MITO-8 showed that prolonging platinum-free interval by introducing non-platinum-based chemotherapy (NPBC) does not improve prognosis of patients with partially platinum-sensitive recurrent ovarian cancer. Quality of life (QoL) was a secondary outcome. Patients and methods: Ovarian cancer patients recurring or progressing 6–12 months after previous platinum-based chemotherapy (PBC) were randomized to receive PBC or NPBC as first treatment. QoL was assessed at baseline, third and sixth cycles, with the EORTC C-30 and OV-28 questionnaires. Mean changes and best response were analysed. Progression-free survival, response rate, and toxicity are also reported for proper interpretation of data. All analyses were based on intention-to-treat. Results: Out of the 215 patients, 151 (70.2%) completed baseline questionnaire, balanced between the arms; thereafter, missing rate was higher in the NPBC arm. At mean change analysis, C30 scores were prevalently worse in the NPBC than PBC arm, statistical significance being attained for emotional functioning, global health status/QoL, fatigue, and dyspnoea (effect sizes ranging from 0.30 to 0.51). Conversely, as for OV28 scale, the other chemotherapy side-effects item was significantly worse with PBC at three and six cycles, with a larger effect size (0.70 and 0.54, respectively). At best response analysis, improvement of emotional functioning and pain and worsening of peripheral neuropathy and other chemotherapy side-effects were significantly more frequent in the PBC arm. Progression-free survival (median 9 versus 5 months, P  = 0.001) and objective response rate (51.6% versus 19.4%, P  = 0.0001) were significantly better with PBC. Allergy, blood cell count, alopecia, nausea, musculoskeletal, and neurological side-effects were more frequent and severe with PBC; hand–foot skin reaction, rash/desquamation, mucositis, and vascular events were more frequent with NPBC. Conclusion: MITO-8 QoL analysis shows that deterioration of some functioning and symptom scales is lower with PBC, with improvement of emotional functioning and pain, despite worsening of toxicity-related items. ClinicalTrials.gov: NCT00657878.